Oppression and Nonhuman Animals - Stoljar, Natalie (Les ateliers de l'éthique / The Ethics Forum, 2024)
This discussion examines the plausibility of applying an oppression framework to the case of nonhuman animals. I identify two conceptions of oppression, which I call the social group conception and the ideological conception. The former is the standard account of oppression advanced by feminist philosophers. On this account, the existence of social groups (gender groups, racial groups) is a necessary condition of oppression. The second approach, which is also drawn from Marxist analysis and critical theory, treats oppression as “pejorative” ideology which is both epistemically and morally criticizable. I argue that the application of the social group conception to nonhuman animals faces explanatory and conceptual obstacles. While the application of the ideological conception is more straightforward, it is difficult to articulate an effective notion of ideology critique for the case of nonhuman animals.